The Strategic Discursive Consciousness Of Latin American Feminine Writing - Pastor Pastor, Brígida M. (Línguas & Letras, 2024)
This article attempts to offer an overview of the socio-historical context that has shaped the voice of the Latin American woman writer. It offers an exposure of feminine literary discourses, which are of great relevance to understand the ‘matriheritage of founding discourses’, revealing the rich textual examples of a wide range of women writers in Latin America, from those very well-established to the lesser known and forgotten. It is in the recent past that women writers gained recognition, filling a vacuum created by their exclusion, allowing the exploration of the transgressive and revolutionary essence of their writings. All these women and their work represent a ‘network of relationships’ which reveal ‘the strategic discursive consciousness’ of Latin American women writers.